Management of foreign body a fish in orohypopharynx - Asyari, Ade; Amany, Esmaralda Nurul (Oto Rhino Laryngologica Indonesiana, 2022)
ABSTRACTBackground: Foreign bodies ingestion in children is very common, and most events occur inchildren between 6 months and 3 years. Alive fish foreign body is a rare case that could lead intoupper airway obstruction. The diagnosis was based on history, clinical and examinations. Purpose: Toreport a case and the management of an alive fish as foreign body in orohypopharynx. Case report: A5 years old boy was brought with alive fish as foreign body in the orohypopharynx. The managementwas foreign body extraction and followed by a rigid esophagoscopy procedure. Clinical question:What is the management of a fish as foreign body in orohypopharynx? Method: Evidence basedliterature study of foreign body fish in orohypopharynx. Result: Management of foreign body a fish inorohypophariynx by extraction and rigid esophagoscopy gave a good result. Conclusion: Precisediagnosis and treatment could prevent any complications caused by foreign body a fish inorohypopharynx. It is important to secure the airway, making sure there is no part of the foreign bodyleft and evaluating the esophagus mucosa. If there is any sign of mucosa injury, nasogastric tube isapplied until the injury heals.ABSTRAKLatar belakang: Tertelan benda asing pada anak sangat umum, sering terjadi, dan palingbanyak terjadi pada usia 6 bulan hingga 3 tahun. Benda asing ikan hidup merupakan kasus yangjarang dan dapat menyebabkan sumbatan jalan nafas atas. Diagnosis berdasarkan anamnesis,pemeriksaan fisik dan radiologi. Tujuan: Melaporkan sebuah kasus tatalaksana benda asing ikanhidup pada orohipofaring. Laporan kasus: Dilaporkan satu kasus seorang anak laki-laki berusia 5tahun dengan benda asing ikan hidup di orohipofaring. Tatalaksana pada kasus ini ialah ekstraksibenda asing dan esofagoskopi kaku. Pertanyaan klinis: Bagaimana tatalaksana kasus benda asingikan di orohipofaring? Metode: Berbasis bukti mengenai benda asing ikan di orohipofaring melaluidatabase Cochrane library, Pubmed Medline, dan pencarian manual. Hasil: Tatalaksana benda asingikan di orohipofaring dengan ekstraksi benda asing dan esofagoskopi kaku memberikan hasil yangbaik. Kesimpulan: Diagnosis dan tatalaksana yang tepat dapat menghindari terjadinya komplikasipada kasus benda asing ikan di orohipofaring. Penting untuk menjaga patensi jalan nafas,memastikan tidak ada bagian dari benda asing yang tertinggal serta mengevaluasi mukosa esofagus.Jika terdapat trauma pada mukosa, pemasangan nasogastric tube dapat dilakukan hingga terjadipenyembuhan luka.